Motivation and Human Resource Development's Impact on Work Spirit - Hadisyah Hadisyah; Muhammad Aqsa (Jurnal Mantik, 2022)
The Palopo City Trade Office, as a public agency that offers services to the community, must improve the quality of such services. The purpose of this research is to examine the link between employee morale, motivation, and human resource development. This is a quantitative study in which data will be collected using questionnaires and evaluated using SPSS. Employee morale was found to have a favorable and significant relationship with the variables of motivation and human resource development. Staff morale can be increased by expanding employee capacity in terms of abilities and knowledge earned via education and training, as well as increasing employee motivation from both within and outside the company.